Remote assessment of verbal memory in MS patients using the California Verbal Learning Test. (March 2018) - Barcellos, Lisa F; Bellesis, Kalliope H; Shen, Ling; Shao, Xiaorong; Chinn, Terrence; Frndak, Seth; Drake, Allison; Bakshi, Nandini; Marcus, Jackie; Schaefer, Catherine; Benedict, Ralph HB
We used the California Verbal Learning Test, Second Edition (CVLT-II), one component of the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS), to determine feasibility of a remote assessment protocol. We compared telephone-administered CVLT-II data from MS patients to data acquired in person from an independent sample of patients and healthy controls. Mixed factor analyses of variance (ANOVAs) showed no significant differences between patient groups, but between-group effects comparing patients and healthy controls were significant. In this study, CVLT-II assessment by conventional in-person and remote telephone assessment yielded indistinguishable results. The findings indicate that telephone-administered CVLT-II is feasible. Further validation studies are underway.